Moses Mendelssohn's metaphysics and aesthetics - Munk, Reinier; SpringerLink (online Services). (Dordrecht Netherlands Springer, 2011)
This book presents an extended dialogue in essay form between specialists in the work of Moses Mendelssohn, and experts in important trends in related late-seventeenth and eighteenth century thought. The first group of contributors explores themes in Mendelssohn's metaphysics and aesthetics, presenting both their internal argumentative coherence and their historical context. The second outlines the context of Mendelssohn's views on specific topics, and describes his contribution to the discussion of them. The essays are organized in four sections. The first pairs two essays on Mendelssohn's theory of language and writing. The second section offers three essays addressing a number of topics in Mathematics and philosophy in Mendelssohn. A group of eight essays follows, dealing with Metaphysics in a historical context. The fourth section presents five essays discussing Mendelssohn's Aesthetics in a historical context. Moses Mendelssohn's Metaphysics and Aesthetics arises from a conference held in Amsterdam in 2009, which gathered numerous authorities to address the central theme. Taken together, these eighteen essays present a sophisticated portrait of Mendelssohn, packed with detail and rich in complexity. - publisher's description.
Preface.- THEORY OF LANGUAGE AND WRITING.- Verbal Disputes in Mendelssohn's "Morgenstunden", D.O. Dahlstrom.- Writing, Dialogue, and Marginal Form: Mendelssohn's Style of Intervention, W. Goetschel.- MATHEMATICS AND PHILOSOPHY.- Mendelssohn, Wolff, and Bernoulli on Probability, E.D. Sylla.- Mendelssohn on Lambert's "Neues Organon?" P. Basso.- Mendelssohn's Euclidean Treatise on Equal Temperament, Henk Visser.- METAPHYSICS IN HISTORICAL CONTEXT.- Moses Mendelssohn on Spinoza, D. Pätzold.- Mendelssohn's Concept of the Human Soul in Comparison With Those of Georg Friedrich Meier and Kant, F. Tomasoni.- Turning the Game against the Idealist: Mendelssohn?s Refutation of Idealism in the "Morgenstunden" and Kant's Replies, C.W. Dyck.- What is the bond? The discussion of Mendelssohn and Kant 1785-1787, R.W. Munk.- Divided by Common Sense: Mendelssohn and Jacobi on Reason and Inferential Justification, P. Franks.- The Year 1786 and "Die Bestimmung des Menschen," or "Popularphilosophie" in Crisis, G. di Giovanni.- Mendelssohn versus Herder on the Vocation of Man, F.C. Beiser.- Free Will and Moral Necessity in Mendelssohn, J. Leilich.- AESTHETICS IN HISTORICAL CONTEXT.- Mendelssohn's Theory of Mixed Sentiments, P. Guyer.- The Eighteenth-Century Rehabilitation of Sensitive Knowledge and the Birth of Aesthetics: Wolff, Baumgarten and Mendelssohn, L.C. Madonna.- Mendelssohn's Spinozistic Alternative to Baumgarten's Pietist Project of Aesthetics, U. Goldenbaum.- Mendelssohn's Response to Burke on The Sublime, A. Koller.- Moses Mendelssohn: Iconoclast, G. Freudenthal.
Electronic reproduction.
Keywords: Mendelssohn, Moses -- 1729-1786.; Metaphysics; Aesthetics; Electronic books